Diplomasi Maritim Indonesia dan Keamanan Kawasan Indo Pasifik - Hakiem, Fadhlan Nur; Mayasari, Mayasari; Abidin, Zainal (Papua Journal of Diplomacy and International Relations, 2025)
The Indo-Pacific is a strategic area and a stage for competition among major powers. The region’s vast potential, connecting two oceans and continents, serves as a highly strategic maritime trade route. This article aims to analyse the extent to which Indonesia’s maritime diplomacy contributes to maintaining security in the Indo-Pacific region. The research adopted a qualitative method with an analytical-descriptive approach. Data collection techniques involved literature studies, while data analysis techniques included data reduction, data presentation, and conclusion drawing. The theoretical framework employed consisted of maritime diplomacy and middle power concepts. The research argues that Indonesia, as a middle power, has utilized the Global Maritime Fulcrum vision as a persuasive diplomatic tool to enhance its influence and contribute to maintaining security in the region. However, the Global Maritime Fulcrum as a model of persuasive maritime diplomacy has been gradually abandoned, shifting towards cooperative maritime diplomacy. Indonesia adopted a more cooperative approach in responding to issues and security dynamics in the region. KEYWORDSGlobal Maritime Fulcrum; Indo-Pacific; Maritime Diplomacy; Middle Power; Security